Long-term outcome of minimally invasive mitral valve annuloplasty in disproportionate mitral regurgitation. (25th November 2020) - Albano, M; Nagumo, S; Vanderheyden, M; Bartunek, J; Collet, C; Balogh, Z; Katbeh, A; Kodeboina, M; Van Camp, G; Penicka, M
Abstract: Background: Hypothetical concept of disproportionate secondary mitral regurgitation (SMR) has been recently introduced to facilitate patient's selection for mitral valve intervention. However, real world data validating this concept are unavailable. Purpose: To investigate long-term effects of minimally invasive mitral valve annuloplasty (MVA) in patients with disproportionate (dSMR) versus proportionate SMR. Methods: The study population consisted of 44 consecutive patients (age 67±9, 5 years; 64% males) on guidelines-directed therapy with advanced heart failure (HF), reduced LV ejection fraction (EF) (32±9, 7%) and SMR undergoing isolated mini-invasive MVA. Patients with organic mitral regurgitation or concomitant myocardial revascularization were excluded. To assess SMR disproportionality, the PISA-derived effective regurgitant orifice area (EROA) and regurgitant volume (RV) were compared to the estimated EROA and RV by using Gorlin formula and pooled real world data. Results: According to EROA, a total of 20 (46%) and 24 (54%) patients, respectively, had dSMR and proportionate SMR (pSMR). According to RV, a total of 17 (39%) had dSMR and 27 (61%) had pSMR. Patients with dSMR showed significantly lower prevalence of male gender and higher prevalence of diabetes mellitus than patients with pSMR (p<0, 001). Moreover, we observed smaller LV end-diastolic volume, larger EROA and RV (both p<0, 01) and higher LV EF (p=0, 02) in the dSMR versus the pSMR group. Other baseline characteristics were similar. During median follow up of 4.39 y (IQR 2, 2–9, 96y), a total of 25 (56%) patients died from any cause while 21 (47%) individuals were readmitted for worsening HF. Patients with dSMR versus pSMR according to both EROA and RV showed significantly lower rate of HF readmissions (both p<0.05) (Figure 1, 2). In Cox regression analysis combining clinical and imaging parameters, dSMR was the only independent predictor of HF readmissions (HR 0.20, 95% CI 0.07–0.60, p=0.004). In contrast, mortality was similar between dSMR and pSMR (NS) with age as the only independent predictor (HR 1, 10; 95% CI 1, 03–1, 18, p=0, 003). Conclusions: Minimally invasive MVA is associated with significant reduction of HF readmissions in patients with dSMR versus pSMR while the mortality is similar. This suggests the importance of other parameters, i.e. age and degree of LV remodeling, to guide clinical management in SMR. Funding Acknowledgement: Type of funding source: None